Integrasi Prinsip Catur Paramita Dalam Pembelajaran Berdiferensiasi Pada Pendidikan Agama Hindu: Studi Kasus Di SMAN 4 Mataram - Rudiarta, I Wayan (Jurnal Penelitian Agama Hindu, 2025)
Differentiated learning can be interpreted as learning that seeks to provide maximum learning services to students. This learning is often referred to as learning that favors students because its implementation refers to mapping students based on learning readiness, learning interests and learning profiles. The implementation of differentiated learning in Hindu Religious Education and Budi Pekerti subjects at the high schools level in Mataram city is still very rare, and one of the schools that implement it is Senior High School 4 Mataram. This study aims to critically analyze the implementation of differentiated learning in Hindu Religious Education and Budi Pekerti subjects at Senior High School 4 Mataram by adopting the Catur paramita approach which comes from the concept of Hinduism. This research was conducted using a descriptive qualitative approach with data collection using observation, interview, and documentation techniques. The collected data were then analyzed through the process of data reduction, data presentation and conclusion drawing. Based on this research, differentiated learning in Hindu Religious Education and Budi Pekerti subjects at SMAN 4 Mataram which is applied to the aspects of process differentiation and product differentiation can maintain student motivation, concentration and learning focus. Through the implementation of differentiated learning with the implementation of the values of catur paramita teachings, the learning process can be more effective.